1998
DOI: 10.1002/(sici)1521-4095(199803)10:5<395::aid-adma395>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Cation Recognition by Self-Assembled Layers of Novel Crown-Annelated Tetrathiafulvalenes

Abstract: The combination of molecular recognition [1] and selfassembly processes [2] offers a powerful route to the development of nanoscale systems that have technological applications as sensors, devices, and switches. [3] Macrocyclic ligands continue to attract widespread attention, [4] especially when complexation of a neutral or ionic guest at one site in the molecule induces a change in the optical [5] or redox properties [6] of the system.The recent incorporation of the electroactive tetrathiafulvalene (TTF) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
58
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 7 publications
6
58
0
Order By: Relevance
“…Relatively recently, Reinhoudt et al (19)(20)(21)(22) and Bryce et al (23,24) reported, almost simultaneously, the incorporation of crownether groups into SAMs and their use as potential metal ion sensors. The Reinhoudt group used electrochemical impedance spectroscopy (EIS) for SAM characterization and to study the ion recognition processes (19)(20)(21)(22).…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Relatively recently, Reinhoudt et al (19)(20)(21)(22) and Bryce et al (23,24) reported, almost simultaneously, the incorporation of crownether groups into SAMs and their use as potential metal ion sensors. The Reinhoudt group used electrochemical impedance spectroscopy (EIS) for SAM characterization and to study the ion recognition processes (19)(20)(21)(22).…”
supporting
confidence: 57%
“…25 and 26). The report by Bryce et al (23,24) described SAMs of crown-annelated tetrathiafulvalene (TTF) derivatives, which showed, by cyclic voltammetry (CV), a redox potential shift of the electroactive, surface-confined, crown-TTF group on ion complexation (23,24). The first TTF-crown SAMs reported by this group were apparently unstable after several electrochemical scans (23).…”
mentioning
confidence: 99%
“…This proposed organisation within the monolayer is not only a function of the behaviour of, and interaction between the molecules themselves, but also the interaction between the molecules and the surface [26]. Stable redox chemistry in self-assembled monolayers of TTF derivatives have been reported by several groups including those of Bryce, Ward, Cooke, Sallé, Echegoyen and Stoddart, where the core TTF moiety is anchored to the surface using a surface active functional group such as an alkyl chain with a thiol end group on Au [13,14,[27][28][29][30], thioctic acid disulfide linkers on Au [31][32][33] and oxide-free hydrogen-terminated Si(1 0 0) surfaces [34]. Non-covalent binding of TTF derivatives on graphite has also been reported where the molecule's core TTF unit has a strong interaction with the -system of the graphite surface; this allows the molecule to orientate parallel to the graphite surface through -interactions [35,36].…”
Section: Introductionsupporting
confidence: 65%
“…The non-aromatic 14 -electron system undergoes aromatisation when going from the neutral species to the dithiolium form in the singly and doubly oxidised states. TTF and its derivatives have featured in a wide variety of applications from crown-ether annelated electrochemical sensors [13][14][15][16], to molecular electronics [17][18][19][20][21] including organic field-effect transistors [22] and other advanced molecular assemblies [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 We recently prepared TEG (triethylene glycol monomethyl ether)-and PEG (polyethylene glycol monomethyl ether)-end-grafted carbosiloxane and carbosilane dendrimers and studied their ability to detect alkali metal-ion binding. 11 The general idea was to use the glycols to form ion binding domains at the periphery (similar to crown ethers) via self assembly.…”
mentioning
confidence: 99%